L2 Phonology Learning among Young-Adult Learners of English: Effects of Regular Classroom-based Instruction and L2 Proficiency - Diana Morales Pech; Jesús Izquierdo (Universidad Autónoma de Baja California, 2011)
Using a mixed methodology, this study examines the impact of a university-level English phonology course on the acquisition of vowel and consonant sounds in that language, by beginning (n = 4), pre-intermediate (n = 8) and intermediate-level (n = 6) students. The 5-hour-a-week, 16-week course was taught by teacher of English. To determine the effects of the course, students participated in two oral activities during an interview at the beginning of the course, and another at the end. During these interview, nine classes were observed, and the instructor reported the activities implemented. The analysis of variance revealed positive changes in all the students' pronunciation students. Observations and reports verified the presence of systematic and focused phonological teaching through a variety of activities. The results suggest that this type of teaching allows students to counteract the negative effects which biological factors and the influence of the mother tongue have on learning.